2013
DOI: 10.4028/www.scientific.net/amr.702.236
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Characterization of p-CdTe/n-Si (111) Heterojunction Diode

Abstract: p-CdTe film has been deposited on n-Si(111) substrate by thermal evaporation technique. The prepared CdTe/Si heterojunction diodes have been annealed at 573K. The capacitance-voltage measurements have studied for the prepared heterojunctions under 2 KHz frequencies. The capacitance-voltage measurement indicated that these diodes are abrupt. The capacitance at zero bias, the built in voltage and the doping concentration increased after annealing process while the zero bias depletion region width is decreased. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…This effect can be corroborated by some research studies. The study by Mohammed Alaani [47] found values of I s between orders of magnitude 10 −8 and 10 −7 and the Bin Lv [48] study found values between orders of magnitude 10 −7 and 10 −5 . As in Figures 8 and 9, our results show a range between 10 −6 and 10 −7 for the clean panel and between 10 −5 and 10 −6 for the panel with the maximum sand density.…”
Section: Impact Of Sand In the Input Parameters Of 1m5pmentioning
confidence: 94%
“…This effect can be corroborated by some research studies. The study by Mohammed Alaani [47] found values of I s between orders of magnitude 10 −8 and 10 −7 and the Bin Lv [48] study found values between orders of magnitude 10 −7 and 10 −5 . As in Figures 8 and 9, our results show a range between 10 −6 and 10 −7 for the clean panel and between 10 −5 and 10 −6 for the panel with the maximum sand density.…”
Section: Impact Of Sand In the Input Parameters Of 1m5pmentioning
confidence: 94%